ACUTE TOXICITY OF NEW COMPOUNDS 12,13-DIHIDRO--AMYRIN-20,30-en-3-ACETAT ; 12-13-DIHIDRO--AMYRIN-20,30-en-3-ol AND -SITOSTAN-20,30-en-3-ol TO Artemia – Salina Leach - Sri Mulyani M. (Indonesian Journal of Pharmacy, 2001)
Acute toxicity assay of new compound from nature resources is very important to be carried out. This research was to perform an acute toxicity assays of new compound from Eupatorium inulifolium H.B.K. Acute toxicity assays was carried out using Brine Shrimp Bioassay method. The result showed that two compounds, 12,13-dihydro--amyrin-20,30-en-3-ol and -sitostan-20,21-en-3-ol displayed toxicity (LC50 < 1000 g/ml), and LC50 of 12,13-dihydro--amyrin-20,30-en-3-acetate was exceeding 1000 g/ml.Key words: 12,13-dihydro--amyrin-20,30-en-3-ol, 12,13-dihydro--amyrin-20,30-en-3-acetate, -sitostan-20,21-en-3-ol, toxicity assay, Artemia salina Leach.